First report of Chilli leaf curl India virus (ChiLCINV) infecting Stachytarpheta jamaicensis in India. (3rd July 2022) - Verma, Raj; Verma, Abhishek; Tripathi, Savarni
Abstract: Blue snakeweed ( Stachytarpheta jamaicensis ) exhibiting symptoms of virus infection such as crinkling, yellowing, mottling, reduction in leaf size and downward curling were observed during disease survey in Pune, Maharashtra, India in 2021. The presence of a begomovirus in the infected plants was confirmed by PCR assay using universal primers and sequence analysis. BLASTn analysis of the sequence of PCR product revealed that it shared 95.55% identity with Chilli leaf curl India virus (ChiLCINV) isolates. In the phylogenetic analysis, the sequence clustered with ChiLCINV isolates reported from various hosts. To our knowledge, this is the first report of a begomovirus (ChiLCINV) infecting S. jamaicensis in India.